2007
DOI: 10.1016/s0010-9452(08)70492-1
|View full text |Cite
|
Sign up to set email alerts
|

Forgetting Due to Retroactive Interference: A Fusion of Müller and Pilzecker's (1900) Early Insights into Everyday Forgetting and Recent Research on Anterograde Amnesia

Abstract: Ebbinghaus' seminal work suggested that forgetting occurred as a function of time. However, it raised a number of fundamental theoretical issues that still have not been resolved in the literature. Müller and Pilzecker (1900) addressed some of these issues in a remarkable manner but their observations have been mostly ignored in recent years. Müller and Pilzecker (1900) showed that the materials and the task that intervene between presentation and recall may interfere with the to-be-remembered items, and they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
192
2
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(217 citation statements)
references
References 38 publications
15
192
2
8
Order By: Relevance
“…Müller &Pilzecker, 1900), andWixted (2004) has proposed that any interfering event can cause the loss of pre-consolidated memories. In support of this, Dewar et al (2007) reported that a range of distractor tasks impair recall in comparison with a no-interference control condition. They asked participants to remember a list of nouns and, during an 8 min retention interval, participants were subjected to different types of distraction in different conditions.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Müller &Pilzecker, 1900), andWixted (2004) has proposed that any interfering event can cause the loss of pre-consolidated memories. In support of this, Dewar et al (2007) reported that a range of distractor tasks impair recall in comparison with a no-interference control condition. They asked participants to remember a list of nouns and, during an 8 min retention interval, participants were subjected to different types of distraction in different conditions.…”
Section: Discussionmentioning
confidence: 84%
“…Recent research continues to replicate this effect (e.g. Della Sala, Cowan, Beschin, & Perini, 2005;Dewar, Cowan, & Della Sala, 2007) and so retention might be similarly aided by a period of wakeful rest that occurs before RI. It has been proposed that delaying interference by employing a rest period allows the memory to become more resistant to subsequent interference (Wixted, 2004) and numerous studies published in the twentieth century explored this "temporal gradient" of RI.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…McGeoch & McDonald, 1931). However, recently both conclusions have been re-evaluated (Dewar et al, 2007;Wixted, 2004; also see Skaggs, 1933). Wixted (2004) for example, makes a distinction between specific retroactive interference (S-RI) and non-specific retroactive 47 CHAPTER 1.…”
Section: Non-specific Retroactive Interferencementioning
confidence: 99%
“…Wixted (2004) suggests that "new learning draws on a limited pool of resources that may have otherwise been available to consolidate the original learning" (p.247). However, a recent experiment suggests that retroactive interference occurs even when no intentional learning is required (Dewar et al, 2007 …”
Section: Non-specific Retroactive Interferencementioning
confidence: 99%